Optimizing Ship-to-Ship (STS) Activities for Effectivity Operations on MT. Gunung Kemala: Optimalisasi Aktivitas Ship-to-Ship (STS) untuk Efektivitas Operasional di MT. Gunung Kemala - Sabaruddin; Muda, Indra; Dahlan, Harris R.; Nurmala, Eka; Aini, Qurratun (PT. Alpha Trianguli Australis, 2025)
The MT. Gunung Kemala ship while anchored in Balikpapan serving as a mother ship experienced damage to the mooring winch which hampered the mooring unmooring process. Obstacles during the STS process can result in losses, such as loading and unloading processes that take a long time, the berthing process that does not run smoothly, and quite high operational costs, MT. Gunung Kemala needs to take effective action to anticipate this. This study uses a qualitative method to examine the factors that influence the optimization of Ship to Ship (STS) activities at MT. Gunung Kemala. The results of this study are: 1) Factors that cause suboptimal Ship to Ship (STS) activities at MT. Gunung Kemala include weather and environmental conditions, coordination and communication, technical conditions of ships and equipment, regulatory and administrative factors, management and planning, and safety and environmental factors; and 2) Efforts made so that Ship to Ship (STS) activities at MT. Mount Kemala is running optimally, including optimizing planning and preparation, fulfilling technical and maintenance aspects, crew training and competence, risk and safety management, improving coordination with related parties, utilizing technology, evaluation and continuous improvement, and environmental management.